In search of an efficient and autonomous study: Approaches in music and the integration through project management (Orfeu, 2021)
The scarcity of time (characteristic of contemporaneity), the dependence on the teacher during the individual study and the generalization of the problems point to the need for an efficient and autonomous study that suits the individual's particularities. Through a literature review in the area of ​​music, we can verify that the existing works are mostly focused on specific problems, usually practical and technical instrumental. From this, we seek to offer musicians a way to integrate all areas of study already addressed by researchers: deliberate practice, organization, planning, self-regulation, strategies and tools. Considering the construction of theories through abstraction (DEWEY, 1920), our proposal is based on project management by translating the main practices into music according to the PMBOK® Guide (PMI, 2017). This is research in progress, so adjustments will be needed.
Keywords: Performance; Autonomy; Efficiency; Integration; Study project management